Septate uterus with hypoplastic left adnexa with cervical duplication and longitudinal vaginal septum: Rare Mullerian anomaly - Aruna Nigam; Manju Puri; Shubha Sagar Trivedi; Barenya Chattopadhyay (Wolters Kluwer Medknow Publications, 2010)
A large analysis of all the studies in the period from 1950 to 2007 suggests that the prevalence of congenital uterine anomalies in the general population is 6.7%; and in the infertile population, 7.3%. We report a rare case of unilateral hypoplastic fallopian tube and ovary with septate uterus, cervical duplication, longitudinal vaginal septum. To the best of our knowledge, this is the first report of such a congregation of anomalies.